Axial and transverse depositional systems of a syn-rift basin fill (Bohai Bay Basin, China). (June 2021) - Wang, Ru; Ji, Youliang; Colombera, Luca; Mountney, Nigel P.; Yuan, Bo; Li, Danjie; Song, Hongyu; Zhou, Sheng
Abstract: For improved prediction of reservoir distribution and quality in the infill of rift basins, it is paramount to characterize the extent and relative dominance of simultaneously active depositional systems fed by axial and transverse drainages, and to understand how these vary in response to geological controls. This study demonstrates how integration of seismic, wireline-log, core, petrographic and heavy-mineral datasets, combined with existing palaeotopographic reconstructions, can be utilized to characterize the spatiotemporal distribution and reservoir potential of syn-rift depositional systems associated with axial and transverse sediment routes to a lacustrine basin. In the Eocene of the Dongpu Depocentre (Bohai Bay Basin, China), three distinct delta types are identified: footwall-derived coarse-grained fan deltas and sand-rich deltas, and axial deltas that are dominated by siltstone and fine sandstone. The spatiotemporal distribution of these systems in the basin fill arose from the interaction of tectonic, lake-level, and climatic controls. Sedimentological and provenance analyses indicate the predominance (>85%) of axial systems over transverse systems in the infill of this elongate, asymmetrical graben. Locally, the interaction and amalgamation of transverse and axial systems was controlled by the presence of intra-basinal highs, through their influence on sediment-delivery pathways, and by high rates of sediment supply that caused overfill of isolated depocentres. Texturally mature, well-sorted fine sandstones of axial deltaic systems, which were sourced from comparatively large catchments, are attractive reservoir targets. By contrast, conglomerates of transverse fan deltas are poorly sorted and have more limited reservoir potential. However, footwall-derived fans may serve as viable reservoir targets locally, where fed by major hinterland drainages associated with long sediment-transport distances. Identification of the position of relay ramps in seismic data and recognition of bedrock-incised drainage outlets on the footwall basement of the basin margin may allow prediction of the presence and location of reservoir units associated with oversized deltas. Highlights: Multidisciplinary study on the stratigraphic architecture of syn-rift basin fills. Volumetric predominance of axial systems over transverse systems in the basin fill. Texturally mature, well-sorted axial deltas act attractive reservoir targets. Poorly sorted transverse fan deltas typically have limited reservoir potential. Locally oversized footwall-derived fans may serve as viable reservoir targets.